Design of a Real-Time Voltage Monitoring System for PLN and Generator Using Telegram and ESP32 - Wahyudi, Ricky; Prabawa, Prabawa; Putra, Reski Eka; Winarta, Fadhel; Fauzan, Reski Yulian (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2025)
In modern society, electricity is essential for both daily life and industrial operations. Frequent power outages in Indonesia frequently cause disruptions to household, office, and industrial operations, especially during periods of high demand. As a solution, generator sets (gensets) are commonly used as backup power sources. However, manual checks are still used in many installations for monitoring and switching between PLN (State Electricity Company) and genset sources, which can raise operational risks and delay response times. While switching is addressed by existing systems like Automatic Transfer Switches (ATS), they typically do not include real-time notifications or integrated remote monitoring. Using an ESP32 microcontroller and PZEM-004T voltage sensors, along with the Telegram Bot API, this study suggests designing and implementing a real-time voltage monitoring system. The system finds the active source, measures voltage from PLN and genset sources, and instantly alerts users via Telegram. In comparison to a calibrated multimeter, performance testing reveals an average notification delay of less than 5 seconds and a voltage reading error margin of less than ±2%. By offering an affordable, scalable, and interactive monitoring solution, the developed system fills in the gaps in earlier research. It improves responsiveness and dependability in settings that need constant electrical monitoring by giving users access to real-time updates on voltage levels and power source status.